Calcifying Bacteria Flexibility in Induction of CaCO3 Mineralization - Darya A. Golovkina; Elena V. Zhurishkina; Lyubov A. Ivanova; Alexander E. Baranchikov; Alexey Y. Sokolov; Kirill S. Bobrov; Alexey E. Masharsky; Natalia V. Tsvigun; Gennady P. Kopitsa; Anna A. Kulminskaya (Life, 2020)
Microbially induced CaCO3 precipitation (MICP) is considered as an alternative green technology for cement self-healing and a basis for the development of new biomaterials. However, some issues about the role of bacteria in the induction of biogenic CaCO3 crystal nucleation, growth and aggregation are still debatable. Our aims were to screen for ureolytic calcifying microorganisms and analyze their MICP abilities during their growth in urea-supplemented and urea-deficient media. Nine candidates showed a high level of urease specific activity, and a sharp increase in the urea-containing medium pH resulted in efficient CaCO3 biomineralization. In the urea-deficient medium, all ureolytic bacteria also induced CaCO3 precipitation although at lower pH values. Five strains (B. licheniformis DSMZ 8782, B. cereus 4b, S. epidermidis 4a, M. luteus BS52, M. luteus 6) were found to completely repair micro-cracks in the cement samples. Detailed studies of the most promising strain B. licheniformis DSMZ 8782 revealed a slower rate of the polymorph transformation in the urea-deficient medium than in urea-containing one. We suppose that a ureolytic microorganism retains its ability to induce CaCO3 biomineralization regardless the origin of carbonate ions in a cell environment by switching between mechanisms of urea-degradation and metabolism of calcium organic salts.